Collective Action, Mutual Aid, and Wetland Agriculture in the Highlands of Papua New Guinea. (17th January 2019) - Denham, Tim
Abstract : Much archaeological and historical theory of societal development characterises societies that are reliant on hydraulic agro-ecosystems as maintaining high levels of socio-political control and centralisation (Wittfogel 1957). In the highlands of Papua New Guinea, large-scale and extensive wetland agricultural practices date from several thousand years ago up to the present. These extensive drainage networks are the product of collective, community-based action and are co-ordinated by the persuasive influence of relatively weak and egalitarian political leaders, big-men (Strathern 1971). Here the New Guinea evidence is used to critique evolutionary models of societal development and associated concepts of human nature to develop a mutualistic perspective on the past. These ideas are pertinent to contemporary highland societies, many of which aggressively maintain their independence from each other and the Papua New Guinea state. Their agricultural history continues as a living tradition into the present.